2016
DOI: 10.1007/s12672-016-0263-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Implementing Gene Expression Classifier on Outcomes of Thyroid Nodules with Indeterminate Cytology

Abstract: Thyroid nodules are classified into six cytological categories under the Bethesda classification system. Two of these categories, atypical of undetermined significance (AUS) and suspicious for a follicular neoplasm (SFN), are further labeled as "indeterminate" diagnosis. Starting in June, 2012, Kansas University-Wichita Endocrine clinic implemented Afirma® Gene Expression Classifier (AGEC) to evaluate the need for surgical resection of thyroid nodules in patients with an indeterminate diagnosis. Electronic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…al. 14 2014 0.42 (0.32-0.51) 1.00 (0.29-1.00) Han et al 15 2014 0.45 (0.23-0.68) 0.00 (0.00-1.00) Lastra et al 16 2014 0.46 (0.31-0.61) 1.00(0.16-1.00) McIver et al 17 2014 0.16 (0.05-0.33) 0.75 (0.19-0.99) Celik et al 18 2015 0.59 (0.33-0.82) 1.00 (0.16-1.00) Noureldine et al 19 2015 0.42 (0.35-0.50) 0.83 (0.52-0.98) Yang et al 20 2015 0.57 (0.44-0.68) 1.00 (0.48-1.00) Zhu et al 21 2015 0.60 (0.26-0.88) 0.00 (0.00-1.00) Abeykoon et al 22 2016 0.86 (0.57-0.98) 0.00 (0.00-1.00) Chaudhary et al 23 2016 0.38 (0.27-0.50) 1.00 (0.63-1.00) Marti et al 6 2016 0.43 (0.30-0.56) 1.00 (0.59-1.00) Sacks et al 24 2016 0.33 (0.21-0.47) 1.00 (0.40-1.00) Witt et al 25 2016 0.40 (0.16-0.68) 0.00 (0.00-1.00) Wu et al 26 sequencing technology in fine-needle aspiration and tissue samples [17]. This method was superseded by a second, improved version of the assay (ThyroSeq v2) [27].…”
Section: Studymentioning
confidence: 99%
“…al. 14 2014 0.42 (0.32-0.51) 1.00 (0.29-1.00) Han et al 15 2014 0.45 (0.23-0.68) 0.00 (0.00-1.00) Lastra et al 16 2014 0.46 (0.31-0.61) 1.00(0.16-1.00) McIver et al 17 2014 0.16 (0.05-0.33) 0.75 (0.19-0.99) Celik et al 18 2015 0.59 (0.33-0.82) 1.00 (0.16-1.00) Noureldine et al 19 2015 0.42 (0.35-0.50) 0.83 (0.52-0.98) Yang et al 20 2015 0.57 (0.44-0.68) 1.00 (0.48-1.00) Zhu et al 21 2015 0.60 (0.26-0.88) 0.00 (0.00-1.00) Abeykoon et al 22 2016 0.86 (0.57-0.98) 0.00 (0.00-1.00) Chaudhary et al 23 2016 0.38 (0.27-0.50) 1.00 (0.63-1.00) Marti et al 6 2016 0.43 (0.30-0.56) 1.00 (0.59-1.00) Sacks et al 24 2016 0.33 (0.21-0.47) 1.00 (0.40-1.00) Witt et al 25 2016 0.40 (0.16-0.68) 0.00 (0.00-1.00) Wu et al 26 sequencing technology in fine-needle aspiration and tissue samples [17]. This method was superseded by a second, improved version of the assay (ThyroSeq v2) [27].…”
Section: Studymentioning
confidence: 99%
“…The performance of GEC testing in 210 nodules categorized as atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS; Bethesda category III) or suspicious for follicular neoplasm (SFN; Bethesda category IV), all of which subsequently had definitive surgical pathology diagnoses, demonstrated a test sensitivity of 90%, specificity of 52%, NPV of 94%, and positive predictive value (PPV) of 37% at a cancer prevalence of 24% . Subsequently, 28 real‐world clinical experience studies have cumulatively reported that only 13% of nodules with GEC benign results underwent surgical resection, a marked reduction compared with the historical treatment of patients with cytologically indeterminate thyroid nodules . In 26 of these studies, only 3% of nodules (50 of 1934 nodules) with GEC benign results were found to be malignant .…”
Section: Introductionmentioning
confidence: 99%
“…Designed to lower patient morbidity and the cost of care by decreasing unnecessary surgery for benign thyroid nodules, the majority of studies have demonstrated the utility of the Afirma GEC, whereas others have questioned the actual cost‐benefit analysis of reflexively incorporating it into clinical care . Behind some of the various interpretations of the performance of the GEC are the inherent differences in agreement among thyroid cytopathologists .…”
Section: The Development Of Thyroid Molecular Testingmentioning
confidence: 99%
“…26,27 Designed to lower patient morbidity and the cost of care by decreasing unnecessary surgery for benign thyroid nodules, the majority of studies have demonstrated the utility of the Afirma GEC, whereas others have questioned the actual cost-benefit analysis of reflexively incorporating it into clinical care. 8,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Behind some of the various interpretations of the performance of the GEC are the inherent differences in agreement among thyroid cytopathologists. 7 However, another concern is the lack of a true "gold standard" in the subsequent validation studies, for which very few of the GEC benign cases have histologic correlation.…”
Section: A "Rule-in" Test: Gene Mutation Panelmentioning
confidence: 99%